Location‐specific cutaneous electrical stimulation of the footsole modulates corticospinal excitability to the plantarflexors and dorsiflexors during standing. Issue 13 (1st July 2022) - Gill, Gagan; Forman, Davis A.; Reeves, Joanna E.; Taylor, Janet L.; Bent, Leah R.
Abstract: Non‐noxious electrical stimulation to distinct locations of the foot sole evokes location‐specific cutaneous reflex responses in lower limb muscles. These reflexes occur at latencies that may enable them to be mediated via a transcortical pathway. Corticospinal excitability to the plantarflexors and dorsiflexors was measured in 16 participants using motor evoked potentials (MEPs). Spinal excitability was measured in eight of the original participants using cervicomedullary motor evoked potentials (CMEPs). Measurements were collected with and without preceding cutaneous stimulus to either the heel (HEEL) or metatarsal (MET) locations of the foot sole, and evoked potentials were elicited to coincide with the arrival of the cutaneous volley at either the motor cortex or spinal cord. Plantarflexor MEPs and CMEPs were facilitated with cutaneous stimulation to the HEEL for MEPs (soleus p  = 0.04, medial gastrocnemius (MG) p  = 0.017) and CMEPs (soleus p  = 0.047 and MG p  = 0.015), but they were unchanged following MET stimulation for MEPs or CMEPs. Dorsiflexor MEPs were unchanged with cutaneous stimulation at either location, but dorsiflexor CMEPs increased with cutaneous stimulation ( p  = 0.05). In general, the increase in CMEP amplitudes was larger than the increase in MEP amplitudes, indicating that an increase in spinal excitability likely explains most of the increase in corticospinal excitability. The larger change observed in the CMEP also indicates that excitability from supraspinal sources likely decreased, which could be due to a net change in the excitability of intracortical circuits. This study provides evidence that cutaneous reflexes from foot sole skin are likely influenced by a transcortical pathway. Abstract : Stimulation of foot sole skin has been shown to contribute significantly to modulation of locomotor muscle activity. Our investigation sought to uncover whether cutaneous stimulation to the heel and metatarsal regions of the foot sole influence measures of corticospinal and spinal excitability, in order to shed light on transcortical control of foot placement during gait. Our results demonstrated that both corticospinal and spinal excitability were elevated following cutaneous stimulation, although this effect differed based on stimulus site and muscle (plantarflexors or dorsiflexors). The findings of this study provide further evidence that transcortical pathways are likely involved in the cutaneous reflex, and they have the potential to drive changes in neurorehabilitative guidelines.